Marcas inovadoras: como os consumidores percebem a inovação - Silva, Cláudio Heleno Pinto da (2016)
The perception of innovation and innovative brands may be differential for the development and survival of many businesses. This dissertation aims to analyze how innovation impacts the brand perception of Brazilian consumers of food products and processed beverages, in addition to identifying brands considered innovative in this industry as well as its features. A total of 369 respondents contributed to the survey, offering 1255 features grouped in 10 categories from the content analysis: Entrepreneurship; Marketing and Communication; Product Mix; Practicality and Functionality; Packaging and Design; Consumer Relations, Management; Social and Environmental Sustainability; Technology and R & D; and New + New Experience. The results were compared to works that address innovation and that could be related to the food and beverage industry, as Beverland et al. (2010); Domingues (2008); Oslo Manual (OECD, 2004); Pavitt (1984); Pleschak and Sabisch (1996) cited by Guo and Yin (2014); and Schumpeter (1982, 1985, 2005). Cross-analysis showed that in general, the innovative brands have a mixing process, union, or mix among the ten characteristics, with an emphasis on three: Entrepreneurship, Marketing and Communications and Product Mix. Overall, the study showed that innovative brands are creative, confident and bold, present creative and interesting advertisements, are affordable, value the quality of their products and seek to satisfy desires, often still unknown by consumers themselves.